Malay-Muslim identity in the era of globalization - Zakaria Stapa (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Extant research findings confirm the conjecture that Muslims in Malaysia in general are very concerned with the surge of globalization, fearing that Islamic values stand to be diluted with non-Islamic influences as a result of this. However, a more careful analysis suggests that globalization is merely a by-product of a more dominant notion and philosophy known as post-modernism. This indicates that postmodernism is the hub of globalization through which its ideologies and cultures are formed. It is also worth noting that post-modernism has also given birth to the latest model of secularism. Therefore, post-modernism, whether in the form of globalization or current version of secularism, is Islam's great enemy as it brings about values, beliefs and lifestyles that completely contradict Islamic teachings. As such, in the context of Muslims in Malaysia today, despite the proliferation of teachings of Islamic values at various levels, both formally and informally, there is still a clear indication that many are still trapped within the ideals of post-modernism. This manifests in the form of serious moral crime, strong beliefs in liberalism and religious pluralism, liberal ethics that champion feminism and homosexuality as well as the lack of respect towards traditional authority. This suggests that Islamic education in Malaysia in its current form is not able to counter the threats of post-modern thinking. Therefore, a new approach in teaching Islamic values must be sought, and in this context, presented from the viewpoint and approaches of sufism and sufi’s order.